Antistatic photocuring coating and preparation method and application thereof
By mixing defoaming and three-roll grinder under vacuum conditions to optimize the gap setting, a single-wall carbon nanotube dispersion system with covalent bonds is formed, which solves the problems of poor appearance and poor anti-static effect of anti-static coatings, and achieves efficient and low-cost coating preparation and excellent optical performance.
Patent Information
- Application Number
- CN202411808734.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing anti-static photocuring coatings have poor appearance during construction, and have appearance defects such as pitting, which cannot meet the optical standards. The anti-static effect is poor, making it difficult to meet the standard to the power of 6.
By mixing and defoaming single-wall carbon nanotubes, polymer dispersant and connecting agent under vacuum conditions, covalent bond connections are formed, the dispersion efficiency of single-wall carbon nanotubes is improved, and the gap setting is optimized in the three-roll grinder is further improved, and the dispersion effect is finally formed in the photocuring resin to form a covalent bond connection, and an excellent anti-static photocuring coating is prepared.
It has achieved good dispersion of anti-static photocuring coatings, excellent coating appearance, no dots, high light transmittance, low surface resistivity, meets optical grade requirements, and has extremely high commercial value.
Smart Images

Figure CN119286295B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocurable coatings, and in particular relates to an antistatic photocurable coating and a preparation method and application thereof. Background Art
[0002] Optical-grade antistatic hardened films are mainly used in 3C electronics, liquid crystal panels, semiconductors, new energy vehicles and other fields. The traditional manufacturing method is to apply a layer of antistatic coating on the surface of the optical-grade film, and then apply a thin layer of hardened coating to achieve the antistatic hardening effect. This method has complex procedures and high costs. Antistatic photocuring coatings can be obtained by adding antistatic materials to photocurable coatings. Applying them to the surface of optical films can obtain antistatic hardened coatings in one step. The process is simple and the cost is low. However, the compatibility between antistatic materials and resins in traditional UV-curable antistatic coatings is poor, and a large amount of solvent needs to be added to stabilize the antistatic materials. During the construction process, the coating formed by the evaporation of the solvent has a poor appearance, and there are appearance defects such as pitting, which cannot meet the optical standards. Connecting the antistatic material to the photocurable resin or monomer through a covalent bond to form an antistatic photocurable resin or monomer can solve appearance problems such as pitting, but the covalent connection between the photocurable resin and the antistatic material causes a poor antistatic effect, which is generally difficult to meet the sixth power standard.
[0003] Single-walled carbon nanotubes are a quasi-one-dimensional tubular nanomaterial that can form a conductive network in the resin, have little effect on transparency, and have stable performance. They are the best material in the field of transparent antistatic materials. However, single-walled carbon nanotubes are difficult to disperse. Usually, a large amount of surfactants need to be added to the solvent medium for dispersion, and then added to the resin of the corresponding solvent system to form an antistatic coating. However, this method still cannot solve problems such as poor appearance.
[0004] Therefore, how to make full use of the performance advantages of single-walled carbon nanotubes, develop an antistatic photocuring coating, and apply this coating to the surface of optical film to obtain a coating with excellent appearance, meeting optical grade requirements and excellent antistatic performance is a technical problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to provide an antistatic photocurable coating and a preparation method and application thereof, so as to solve the problems in the background technology.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing an antistatic photocurable coating comprises the following steps:
[0008] Step S1, first placing the single-walled carbon nanotubes, the polymer dispersant and the linking agent in a special container of a degassing machine, mixing and degassing them under vacuum conditions, then adding a photocurable resin into the special container, and mixing and degassing them again under vacuum conditions to obtain a mixture;
[0009] Step S2, transferring the mixture to a three-roll mill, setting the gap between rollers 1 and 2 to 20-300 μm, and the gap between rollers 2 and 3 to 10-150 μm, grinding and dispersing at a rotation speed of 500 rpm for 1-3 times to obtain an antistatic photocurable resin with well-dispersed single-walled carbon nanotubes;
[0010] Step S3, fully and uniformly mixing the antistatic photocurable resin, the photocurable monomer, the initiator and the auxiliary agent to obtain the antistatic photocurable coating.
[0011] It should be noted that the operation sequence in step S1 has a significant impact on the performance of the antistatic photocurable coating; first, the single-walled carbon nanotubes, polymer dispersants and linkers are mixed and degassed to achieve sufficient mixing, and then the photocurable resin is added and mixed and degassed, so that the polymer dispersants and linkers can be more fully contacted and infiltrated into the single-walled carbon nanotube bundles, and the opened single-walled carbon nanotube bundles can remain stable for a long time under the steric hindrance of the photocurable resin.
[0012] It should also be noted that the operations of step S1 to step S3 must be completed in a yellow light operation room to avoid the influence of ultraviolet rays on the resin performance and the operation process.
[0013] Furthermore, in step S1, the mass ratio of the photocurable resin, the single-walled carbon nanotubes, the polymer dispersant and the connecting agent is (50-75): (5-10): (15-30): (5-10).
[0014] Furthermore, the photocurable resin is an acrylate type UV resin; specifically, the photocurable resin can be one or more of polyurethane acrylate, polyester acrylate, polyether acrylate and epoxy acrylate; and the photocurable resin does not contain solvents and photocurable monomers; the photocurable resin may contain a trace amount of inhibitor to prevent the photocurable resin from undergoing self-crosslinking reaction; the viscosity of the photocurable resin is 3000-8000mPa·s; the photocurable resin can be selected according to application characteristics, such as hardness, wear resistance, yellowing characteristics, smoothness, stretchability, etc.
[0015] Furthermore, the purity of the single-walled carbon nanotubes is greater than 60%, and may contain a small amount of amorphous carbon, metal catalyst particles, double-walled carbon nanotubes or multi-walled carbon nanotubes; preferably, the content of multi-walled carbon nanotubes in the single-walled carbon nanotubes is not higher than 10wt%, and the content of metal impurities is not higher than 30wt%; more preferably, high-purity single-walled carbon nanotube powder is used, and the purity is greater than 98.5%; the purity of the single-walled carbon nanotubes has a certain influence on the conductivity and transmittance of the antistatic photocurable resin. The higher the purity of the single-walled carbon nanotubes, the less the mass fraction of the single-walled carbon nanotubes required to be added under the premise of the same antistatic performance, and the higher the transmittance.
[0016] Furthermore, the polymer dispersant is a combination of one or both of an acrylate copolymer and an amino acid ester copolymer; specifically, the polymer dispersant is selected from BYK191, BYK190, BYK181, BYK154, BYK187, BYK194N, BYK199, BYK156, etc. of BYK Chemical and Lubrizol 20000, Lubrizol 22000 and Lubrizol 24000; the active ingredient of the polymer dispersant is 100%, and it is solvent-free; the function of the dispersant is to open the single-walled carbon nanotube bundle under a certain shear force to achieve good dispersion of the single-walled carbon nanotubes.
[0017] Furthermore, the linker is one or a mixture of maleimide-polyethylene glycol (MAL-PEG), maleimide-polyethylene glycol-active ester (NHS-PEG-MAL), active ester-polyethylene glycol-active ester (NHS-PEG-NHS); the role of the linker is to improve the bonding force between the polymer dispersant and the single-walled carbon nanotubes.
[0018] Furthermore, the vacuum degree of the mixed degassing is -30 to -80 kPa, the rotation speed of the mixed degassing is 1500-2000 rpm, and the time of the mixed degassing is 3-10 minutes. The purpose of vacuuming is to discharge bubbles in the powder in a high viscosity system so that the dispersant and the connector can penetrate into the tube bundle.
[0019] Furthermore, the mass ratio of the antistatic photocurable resin, the photocurable monomer, the initiator and the auxiliary agent is (20-50): (43-73): 5: 2. The initiator is one or a mixture of photoinitiator 184, photoinitiator 1173, and photoinitiator TPO; the auxiliary agent includes but is not limited to a leveling agent or a wetting agent, specifically selected from BYK Chemical leveling agent BYK333.
[0020] Further, the functionality of the photocurable monomer is 1-6, including but not limited to one or more of pentaerythritol triacrylate (PETA), acryloyl morpholine (ACMO), dicyclopentenyl acrylate (DCPA), 1,6-hexanediol diacrylate (HDDA), 1,4-butanediol diacrylate (BDDA), trimethylolpropane triacrylate (TMPTA), and dipentaerythritol hexaacrylate (DPHA);
[0021] An antistatic photocurable coating is prepared by the above preparation method. The viscosity of the antistatic photocurable coating is 1000-5000 mPa·s.
[0022] An application of an antistatic photocurable coating in an optical film comprises the following steps:
[0023] The antistatic photocurable coating is applied to the surface of the PET base film with a scraper, and after UV curing under a curing lamp, an antistatic PET hardened film is obtained.
[0024] Beneficial effects:
[0025] The present invention innovatively proposes to promote the dispersion of single-walled carbon nanotubes in a photocurable resin by assisting a polymer dispersant with a connector. First, the single-walled carbon nanotubes, the polymer dispersant and the connector are mixed and degassed. A strong force is formed between the single-walled carbon nanotubes and the polymer dispersant through the coupling of the connector, which greatly improves the dispersion efficiency of the single-walled carbon nanotubes. Then, a photocurable resin with an appropriate molecular weight is added for mixing and degassed. The connector can effectively bridge the single-walled carbon nanotube bundle with the photocurable resin, and use the low fluidity and high molecular weight of the photocurable resin to form a stable steric hindrance, effectively preventing the dispersed single-walled carbon nanotube bundle from agglomerating and precipitating in the coating system. The connector and the polymer dispersant can achieve a synergistic dispersion effect, which greatly improves the surface pitting phenomenon of the coating.
[0026] The present invention utilizes three-roll grinding to prepare an antistatic photocurable resin, and by optimizing the gap between the three rollers, an antistatic photocurable resin with well-dispersed single-walled carbon nanotubes is obtained, which is then used to prepare an antistatic photocurable coating with excellent performance; the preparation method of the present invention is simple and efficient, has a low production cost, and is easy to realize large-scale production;
[0027] The present invention applies the prepared antistatic photocuring coating to the surface of the optical film, and adopts a conventional UV curing process to form a coating on the surface of the PET base film, thereby obtaining an antistatic PET hardened film with low surface resistivity, and the antistatic PET hardened film has a beautiful appearance without pitting, high light transmittance, low haze, high hardness and good adhesion of the surface coating, which can meet various application scenarios with high requirements on the optical properties of the antistatic PET hardened film, and has extremely high commercial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The present invention will be further described below in conjunction with the accompanying drawings.
[0029] Figure 1 This is a scanning electron microscope image of a coating formed after the antistatic photocurable coating prepared in Example 5 of the present invention is coated on the surface of a PET base film. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The single-walled carbon nanotubes used in the embodiments of the present invention are independently produced by the applicant according to the chemical vapor deposition method. The single-walled carbon nanotubes produced have a diameter of 1.6 nm, a length of 30-50 um, and a purity of 75%.
[0032] Example 1
[0033] This embodiment provides an antistatic photocurable coating, which is prepared by the following steps:
[0034] Step S1, first weigh 5g of single-walled carbon nanotubes, 15g of polymer dispersant (Lubrizol 24000) and 5g of linker (NHS-PEG-MAL) and place them in a special container of a degassing machine, mix and degas for 10 minutes under the conditions of vacuum degree of -30kPa and rotation speed of 1500rpm, then add 75g of photocurable resin (purchased from Mitsubishi Chemical, model 7605) into the special container, and mix and degas for 10 minutes under the conditions of vacuum degree of -30kPa and rotation speed of 1500rpm to obtain a mixture;
[0035] Step S2, transferring the mixture to a three-roll mill, setting the gap between roller No. 1 and roller No. 2 to 300 μm, and the gap between roller No. 2 and roller No. 3 to 150 μm, grinding and dispersing at a rotation speed of 500 rpm for 3 times to obtain an antistatic photocurable resin;
[0036] Step S3, 50 g of antistatic photocurable resin, 43 g of DCPA, 5 g of photoinitiator 184 and 2 g of leveling agent BYK333 are fully mixed to obtain an antistatic photocurable coating.
[0037] Example 2
[0038] This embodiment provides an antistatic photocurable coating, which is prepared by the following steps:
[0039] Step S1, first weigh 6.5g of single-walled carbon nanotubes, 20g of polymer dispersant (BYK190 from BYK Chemical) and 6.5g of linker (MAL-PEG) and place them in a special container of a degassing machine, mix and degas for 9 minutes under the conditions of vacuum degree of -45kPa and rotation speed of 1600rpm, then add 67g of photocurable resin (purchased from Mitsubishi Chemical, model 7605) into the special container, mix and degas for 9 minutes under the conditions of vacuum degree of -45kPa and rotation speed of 1600rpm, and obtain a mixture;
[0040] Step S2, transferring the mixture to a three-roll mill, setting the gap between roller No. 1 and roller No. 2 to 150 μm, and the gap between roller No. 2 and roller No. 3 to 75 μm, grinding and dispersing at a rotation speed of 500 rpm for 3 times to obtain an antistatic photocurable resin;
[0041] Step S3, 40 g of antistatic photocurable resin, 53 g of BDDA, 5 g of photoinitiator 1173 and 2 g of leveling agent BYK333 are fully mixed to obtain an antistatic photocurable coating.
[0042] Example 3
[0043] This embodiment provides an antistatic photocurable coating, which is prepared by the following steps:
[0044] Step S1, first weigh 8g of single-walled carbon nanotubes, 24g of polymer dispersant (Lubrizol 24000) and 8g of linker (NHS-PEG-NHS) and place them in a special container of a degassing machine, mix and degas for 8min under the conditions of vacuum degree of -60kPa and rotation speed of 1700rpm, then add 60g of photocurable resin (purchased from Mitsubishi Chemical, model 7605) into the special container, mix and degas for 8min under the conditions of vacuum degree of -60kPa and rotation speed of 1700rpm, to obtain a mixture;
[0045] Step S2, transferring the mixture to a three-roll mill, setting the gap between roller No. 1 and roller No. 2 to 50 μm, and the gap between roller No. 2 and roller No. 3 to 25 μm, grinding and dispersing the mixture twice at a rotation speed of 500 rpm to obtain an antistatic photocurable resin;
[0046] Step S3, 30 g of antistatic photocurable resin, 63 g of PETA, 5 g of photoinitiator TPO and 2 g of leveling agent BYK333 are fully mixed to obtain an antistatic photocurable coating.
[0047] Example 4
[0048] This embodiment provides an antistatic photocurable coating, which is prepared by the following steps:
[0049] Step S1, first weigh 10g of single-walled carbon nanotubes, 30g of polymer dispersant (BYK190 from BYK Chemical) and 10g of linker (NHS-PEG-MAL) and place them in a special container of a degassing machine, mix and degas for 5min under the conditions of vacuum degree of -70kPa and rotation speed of 1900rpm, then add 50g of photocurable resin (purchased from Mitsubishi Chemical, model 7605) into the special container, mix and degas for 5min under the conditions of vacuum degree of -70kPa and rotation speed of 1900rpm, to obtain a mixture;
[0050] Step S2, transferring the mixture to a three-roll mill, setting the gap between roller No. 1 and roller No. 2 to 20 μm, and the gap between roller No. 2 and roller No. 3 to 10 μm, grinding and dispersing the mixture twice at a rotation speed of 500 rpm to obtain an antistatic photocurable resin;
[0051] Step S3, 20 g of antistatic photocurable resin, 73 g of DPHA, 5 g of photoinitiator 184 and 2 g of leveling agent BYK333 are fully mixed to obtain an antistatic photocurable coating.
[0052] Example 5
[0053] This embodiment provides an antistatic photocurable coating, which is prepared by the following steps:
[0054] Step S1, first weigh 10g of single-walled carbon nanotubes, 30g of polymer dispersant (BYK190 from BYK Chemical) and 10g of linker (NHS-PEG-MAL) and place them in a special container of a degassing machine, mix and degas for 3min under the conditions of vacuum degree of -80kPa and rotation speed of 2000rpm, then add 50g of photocurable resin (purchased from Mitsubishi Chemical, model 7605) into the special container, mix and degas for 3min under the conditions of vacuum degree of -80kPa and rotation speed of 2000rpm, to obtain a mixture;
[0055] Step S2, transferring the mixture to a three-roll mill, setting the gap between roller No. 1 and roller No. 2 to 20 μm, and the gap between roller No. 2 and roller No. 3 to 10 μm, grinding and dispersing once at a rotation speed of 500 rpm to obtain an antistatic photocurable resin;
[0056] Step S3, 30 g of antistatic photocurable resin, 63 g of PETA, 5 g of photoinitiator 184 and 2 g of leveling agent BYK333 are fully mixed to obtain an antistatic photocurable coating.
[0057] Comparative Example 1
[0058] The difference between this comparative example and Example 5 is that the amount of single-walled carbon nanotubes used in step S1 is 3 g, and the other raw materials and steps are the same.
[0059] Comparative Example 2
[0060] The difference between this comparative example and Example 5 is that no polymer dispersant is added in step S1, and the other raw materials and steps are the same.
[0061] Comparative Example 3
[0062] The difference between this comparative example and Example 5 is that no linking agent is added in step S1, and the other raw materials and steps are the same.
[0063] Comparative Example 4
[0064] The difference between this comparative example and Example 5 is that in step S1, the photocurable resin is added into a dedicated container of the degassing machine together with the single-walled carbon nanotubes, the polymer dispersant and the linker, and then the mixing and degassing is performed only once, and the remaining steps are the same.
[0065] Comparative Example 5
[0066] The difference between this comparative example and Example 5 is that in step S1, the photocurable resin is replaced by PETA in equal amount, and the remaining steps are the same.
[0067] Comparative Example 6
[0068] The difference between this comparative example and Example 5 is that vacuum degassing is not performed in step S1, and the remaining steps are the same.
[0069] The antistatic photocurable coatings prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were applied to the surface of a 125 μm PET base film with a scraper. The coating thickness was 25 μm. The curing energy was 600 mJ / cm 2 UV curing was performed under 400 °C, and then the coating was tested for performance, the coating appearance was observed and recorded, and the surface resistivity, transmittance, haze, hardness and adhesion of the coating were measured; among them, since the transmittance of the PET base film was 92%, the transmittance of the coating was the measured transmittance / 92%; the results are shown in Table 1:
[0070] Table 1
[0071]
[0072] It can be seen from the data in Table 1 that the surface resistivity of the coating formed by curing the antistatic photocurable coatings prepared in Examples 1 to 5 on the surface of the PET base film is between 10 4 -10 6 Ω / m 2 Within the range, there are no pitting on the coating surface, and the transmittance and haze can meet the optical grade requirements. Figure 1It can be seen more clearly that the coating surface is smooth without visible pitting, and the edge section of the coating shows that the single-walled carbon nanotubes are evenly embedded in the coating, with good dispersion. In addition, the coating also exhibits excellent hardness and adhesion.
[0073] It can be seen from Comparative Examples 1 to 3 that when the amount of single-walled carbon nanotubes is lower than the range of the present application, the antistatic effect drops sharply, because the single-walled carbon nanotubes fail to form an effective conductive network in the coating; polymer dispersants and connectors both play a vital role in the formulation, and both are indispensable, because in the formulation system, the two can play a synergistic dispersion effect, and the connector can enhance the bonding force between the polymer dispersant and the single-walled carbon nanotubes and improve the pitting phenomenon. In addition, as the amount of single-walled carbon nanotubes used increases, the amount of polymer dispersants and connectors used must also increase to ensure a good dispersion effect.
[0074] It can be seen from Comparative Example 5 that when the photocurable resin in the formula is not properly selected (viscosity or molecular weight), the dispersion effect will also be affected. This is because the photocurable resin with the appropriate molecular weight has a strong steric effect on the dispersed single-walled carbon nanotube bundles, which can prevent the bundles from agglomerating to form tiny particles.
[0075] It can be seen from Comparative Examples 4 and 6 that the dispersion process also has a significant impact on product performance. Vacuuming can expel the bubbles in the single-walled carbon nanotubes, making it easier for the linker and the polymer dispersant to infiltrate the surface of the carbon nanotubes, thereby improving the dispersion effect. Adding the photocurable resin too early will cause a portion of the polymer dispersant and the linker to dissolve in the photocurable resin, thereby failing to fully infiltrate the single-walled carbon nanotubes, resulting in a poor dispersion effect and affecting the final performance of the coating.
[0076] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an antistatic photocurable coating, characterized in that: The following steps are involved: Step S1, first placing single-walled carbon nanotubes, polymer dispersants and connectors in a degassing machine, and performing mixing and degassing under vacuum conditions, so that the polymer dispersants and connectors can be more fully in contact with and infiltrate the single-walled carbon nanotube bundles, then adding photocurable resin to the degassing machine, and performing mixing and degassing under vacuum conditions again, the opened single-walled carbon nanotube bundles can remain stable for a long time under the steric hindrance of the photocurable resin, and a mixture is obtained; the polymer dispersant is a combination of one or two of acrylic acid ester copolymers and amino acid ester copolymers, and the function of the dispersant is to open the single-walled carbon nanotube bundles under the action of shear force to achieve good dispersion of the single-walled carbon nanotubes; the connector is a mixture of one or more of maleimide-polyethylene glycol, maleimide-polyethylene glycol-active ester, and active ester-polyethylene glycol-active ester, and the function of the connector is to improve the binding force between the polymer dispersant and the single-walled carbon nanotubes; Step S2, transferring the mixture to a three-roll mill, setting the gap between roller No. 1 and roller No. 2 to 20-300 μm, and the gap between roller No. 2 and roller No. 3 to 10-150 μm, grinding and dispersing at a rotation speed of 500 rpm for 1-3 times to obtain an antistatic photocurable resin; Step S3, uniformly mixing the antistatic photocurable resin, the photocurable monomer, the initiator and the auxiliary agent to obtain the antistatic photocurable coating.
2. The method for preparing an antistatic photocurable coating according to claim 1, characterized in that: The mass ratio of the photocurable resin, the single-walled carbon nanotubes, the polymer dispersant and the connecting agent in step S1 is 50-75:5-10:15-30:5-10.
3. The method for preparing an antistatic photocurable coating according to claim 1, characterized in that: The light-curable resin is an acrylate-type UV resin; the viscosity of the light-curable resin is 3000-8000 mPa·s.
4. The method for preparing an antistatic photocurable coating according to claim 1, characterized in that: The vacuum degree of the mixed degassing is -30 to -80 kPa, the rotation speed of the mixed degassing is 1500 to 2000 rpm, and the time of the mixed degassing is 3 to 10 min.
5. The method for preparing an antistatic photocurable coating according to claim 1, characterized in that: The mass ratio of the antistatic photocurable resin, photocurable monomer, initiator and auxiliary agent is 20-50:43-73:5:2; the initiator is one or a mixture of photoinitiator 184, photoinitiator 1173 and photoinitiator TPO; the auxiliary agent is a leveling agent or a wetting agent.
6. The method for preparing an antistatic photocurable coating according to claim 1, characterized in that: The photocurable monomer is one or more of pentaerythritol triacrylate, acryloyl morpholine, dicyclopentenyl acrylate, 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate, trimethylolpropane triacrylate, and dipentaerythritol hexaacrylate.
7. An antistatic photocurable coating, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6; the viscosity of the antistatic photocurable coating is 1000-5000 mPa·s.
8. The use of an antistatic photocurable coating in an optical film according to claim 7, characterized in that: The following steps are involved: The antistatic photocurable coating is applied to the surface of the PET base film with a scraper, and after UV curing, an antistatic PET hardened film is obtained.
Citation Information
Patent Citations
Preparation method of efficient heat-conducting coating
CN114292586A